On the Whittle Estimator of the Parameter of Spectral Density of Random Noise in the Nonlinear Regression Model - Ivanov, O. V.; Prykhod’ko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
We consider a nonlinear regression model with continuous time and establish the consistency and asymptotic normality of the Whittle minimum contrast estimator for the parameter of spectral density of stationary Gaussian noise.